2020
DOI: 10.29252/jhehp.6.2.7
|View full text |Cite
|
Sign up to set email alerts
|

The Antioxidant Potential and Antihyperlipidemic Activity of Myristica fragrans Seed (Nutmeg) Extract in Diabetic Rats

Abstract: Background: The present study aimed to assess the phenolic content and in-vitro antioxidant capacity of the petroleum ether extract of nutmeg, as well as its antioxidant and antihyperlipidemic activities in alloxan-induced diabetic rats. Methods: Forty-eight male rats were allocated into six groups of eight each: non-diabetic control, diabetic control, and diabetic rats receiving 50, 100 and 200 mg/kg of the nutmeg petroleum ether extract or 100 mg/kg metformin. The in vitro antioxidant activity of the extract… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 22 publications
0
3
0
Order By: Relevance
“…These values were kept at or close to normal by nutmeg extract pretreatment and were 1.86%, 5.54%, 5.65%, and 0.30% for cholesterol, triglycerides, FA, and PL, respectively. (Pashapoor et al, 2020) discovered that giving nutmeg extract to diabetic rats (100 and 200 mg/kg) significantly decreased their levels of malondialdehyde, total cholesterol, triglycerides, and lowdensity lipoprotein while significantly increasing their levels of high-density lipoprotein cholesterol and total antioxidant capacity. (Sompong et al, 2016), demonstrated that Syzygium aromaticum significantly suppressed pancreatic cholesterol esterase activity 1.07% at a dosage of 1 mg/mL.…”
Section: Discussionmentioning
confidence: 99%
“…These values were kept at or close to normal by nutmeg extract pretreatment and were 1.86%, 5.54%, 5.65%, and 0.30% for cholesterol, triglycerides, FA, and PL, respectively. (Pashapoor et al, 2020) discovered that giving nutmeg extract to diabetic rats (100 and 200 mg/kg) significantly decreased their levels of malondialdehyde, total cholesterol, triglycerides, and lowdensity lipoprotein while significantly increasing their levels of high-density lipoprotein cholesterol and total antioxidant capacity. (Sompong et al, 2016), demonstrated that Syzygium aromaticum significantly suppressed pancreatic cholesterol esterase activity 1.07% at a dosage of 1 mg/mL.…”
Section: Discussionmentioning
confidence: 99%
“…In a study by Rahman et al [30], the total phenolic content in four nutmeg seed samples ranged from 0.174 to 1.891 mg GAE/100 g. Sulaiman and Ooi [31] documented a lower total phenolic content (46.3 mg GAE/g) in an 80% methanol extract of nutmeg seeds as compared to the value reported in our study. Pashapoor et al [32] reported total phenolic and flavonoid levels in the petroleum ether of nutmeg seeds of 112.41 mg GAE/100g dry weight (DW) and 26.12 mg quercetin equivalents (QE)/100 g DW, respectively. The concentration of total phenolics in our samples was higher than those observed by Waman et al [33] for various acetone:methanol 1:1 seed extracts, which ranged between 2.34-3.71 mg GAE/g.…”
Section: Total Phenolic and Flavonoid Contentsmentioning
confidence: 99%
“…It was also mentioned in some literature to be a native plant from Banda Island in the Moluccas which is one of the regions in Eastern Indonesia and also important to note that almost half of the world's nutmeg is supplied from the country (Ibrahim et al 2020;Kumari et al 2021). Moreover, the bioactive compounds in nutmeg seeds including the oil and essential oil have been investigated for their potential application as antidiabetic (Pashapoor et al 2020), and in medical sciences (Ibrahim et al 2020;Weerakoon et al 2021).…”
Section: Determination Of Fatty Acids In Nutmeg Seed Oilmentioning
confidence: 99%